2020
DOI: 10.1093/bjsopen/zraa027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bodyweight-adjusted antimicrobial prophylaxis on surgical-site infection rates

Abstract: Background Antimicrobial prophylaxis (AMP) adjustment according to bodyweight to prevent surgical-site infections (SSI) is controversial. The impact of weight-adjusted AMP dosing on SSI rates was investigated here. Methods Results from a first study of patients undergoing visceral, vascular or trauma operations, and receiving standard AMP, enabled retrospective evaluation of the impact of bodyweight and BMI on SSI rates, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Currently, double-dose SAP administration has been shown to reduce SSI for patients weighing at least 120 kg, but all studies had sample sizes of less than 200 patients . In line with these findings, preliminary data suggest a role of double-dose SAP in reducing the SSI rate in patients who weigh at least 80 kg . Nevertheless, in most guidelines for SSI prevention, the issue of weight-adjusted SAP dosing is still considered unresolved …”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Currently, double-dose SAP administration has been shown to reduce SSI for patients weighing at least 120 kg, but all studies had sample sizes of less than 200 patients . In line with these findings, preliminary data suggest a role of double-dose SAP in reducing the SSI rate in patients who weigh at least 80 kg . Nevertheless, in most guidelines for SSI prevention, the issue of weight-adjusted SAP dosing is still considered unresolved …”
Section: Introductionmentioning
confidence: 92%
“…27 Our results did not confirm a preliminary study that suggested an approximately 4-fold lower SSI risk among patients weighing at least 80 kg who received a double cefuroxime dose. 16 The 4-fold lower rate is unlikely to be physiological, and therefore, previous studies may not have corrected for significant, unrecognized bias.…”
Section: Internal and External Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…108 Adjust dosing based on patient weight, 73 according to the following examples: For cefazolin, use 30–40 mg/kg for pediatric patients, use 2 grams for patients weighing ≤120 kg, and 3 grams for patients weighing >120 kg. 109,110 Although data are conflicting regarding the role of 3 grams of cefazolin dosing in reducing SSI in obese patients, multiple studies have shown a benefit compared to 2-gram dosing in this patient population, 110112 with few adverse events from a single dose of 3 grams versus 2 grams of cefazolin. Although some hospitals use 1 gram for adult patients weighing ≤80 kg, there is no harm associated with giving a 2-gram dose. Dose vancomycin at 15 mg/kg.…”
Section: Section 4: Recommended Strategies To Prevent Ssimentioning
confidence: 99%
“…A larger study population would have probably identified known risk factors for SSI, such as BMI or ASA score. [46][47][48] Indeed, a major limitation of this study is the relatively small number of cases compared to the very low incidence of the observed SSI. Thus, we observed no SSI in the PAP or control group.…”
Section: Discussionmentioning
confidence: 99%